Corrosion behavior of api 5l x70 carbon steels in hydrogen sulfide environments - Macedo, Jonas Fernando [UNESP]; Fioravante, Igor Alexandre [UNESP]; Nakazato, Roberto Zenhei [UNESP]; Acciari, Heloisa Andréa [UNESP]; Codaro, Eduardo Norberto [UNESP] (My University, 2021)
As we all know, corrosion of pipelines by hydrogen sulfide is the most worrying factor in the production and transport of oil and gas. In this work the corrosion behavior of API 5L X70MS and X70MO low carbon steels in hydrogen sulfide environment was investigated. Hydrogen induced cracking and sulfide stress cracking tests were carried out according to NACE TM0177 standard. After testing, blisters and cracks were observed only in X70MO steel, probably due to its lower grain refinement and banded microstructure. Internal cracks seem to be initiated in the elongated MnS inclusions. Corrosion process was studied by obtaining potentiodynamic polarization curves, which were registered after open circuit potential measurements, at room temperature. Both steels showed general corrosion in NACE 177A solutions, but the corrosion rate values in H2S-saturated solution were about an order of magnitude higher than the ones in deaerated solution. Hydrogen permeation was characterized in accordance with ASTM G148 standard. In deaerated H2SO4 solution, permeation measurements were similar for both steels. In H2S-saturated solution, X70 MO exhibited higher hydrogen oxidation current values than X70 MS. H2S seems to promote the reduction of protons and increase the concentration of hydrogen atoms in the solution/steel interface, favoring the diffusion process. As X70MO has a coarse microstructure, it offers more pathways for hydrogen diffusion.
Keywords: Hydrogen induced cracking; Low carbon steel; Sour corrosion; Sulfide stress cracking; X70 steel